### A good answer might be:

( 8, 4, 6 )^{T} + ( 2, -2, 9 )^{T} = ( 10, 2, 15 )^{T}
( 2, -2, 9 )^{T} + ( 8, 4, 6 )^{T} = ( 10, 2, 15 )^{T}

# Commutative

Matrix addition is **commutative**.
This means that

**a + b = b + a**.

This works for both row and column matrices of all dimensions.
It is also true that:

**a + b + c = b + c + a = c + a + b = ....**.

In other words, the order in which you add matrices does
not matter.
At least for addition, matrices work the same way as
numbers, since, of course, 1 + 2 = 2 + 1.

Matrices and numbers usually do NOT work the same way!
But they do for addition.

### QUESTION 5:

Contemplate this problem:

( -1, -2, 3 )^{T} + ( 1, 2, -3 )^{T} =